PSYCHOLOGICAL TRAINING IN FOOTBALL - Abdimuratov Muratbay Uzakbergenovich (Web of Journals Publishing, 2024)
Questions of differential sports psychology are considered. The general and specific indices of sportsmen's adaptation were revealed. The psychological characteristics of football players that influence the success of psychological adaptation to the conditions of competitive activity are revealed.
Keywords: football, differential sports psychology, psychological adaptation, adaptation indicators, adaptability criteria, competitive activity conditions.